2018
DOI: 10.4132/jptm.2018.04.04
|View full text |Cite
|
Sign up to set email alerts
|

The Major Role of NF-κB in the Depth of Invasion on Acral Melanoma by Decreasing CD8+ T Cells

Abstract: BackgroundThe tumor microenvironment including immune surveillance affects malignant melanoma (MM) behavior. Nuclear factor κB (NF-κB) stimulates the transcription of various genes in the nucleus and plays a role in the inflammatory process and in tumorigenesis. CD8+ T cells have cytotoxic properties important in the elimination of tumors. However, inhibitory receptors on the cell surface will bind to programmed death-ligand 1 (PD-L1), causing CD8+ T cells to lose their ability to initiate an immune response. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 32 publications
1
13
1
Order By: Relevance
“…Several studies have shown that the increased activity of NF-kB will stimulate the expression of COX-2 inflammatory factors. 8,19 The result of this study is consistent with Usman et al's research which states that there is an association between NF-κβ and CD8 and the depth of invasion of AM. An increase in NF-κβ which is a transcription factor plays a role in stimulating COX-2 expression so that the amount increases.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…Several studies have shown that the increased activity of NF-kB will stimulate the expression of COX-2 inflammatory factors. 8,19 The result of this study is consistent with Usman et al's research which states that there is an association between NF-κβ and CD8 and the depth of invasion of AM. An increase in NF-κβ which is a transcription factor plays a role in stimulating COX-2 expression so that the amount increases.…”
supporting
confidence: 92%
“…Several studies have shown that the increased activity of NF-kB will stimulate the expression of COX-2 inflammatory factors. 8 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations